Manajemen dan Rekayasa Lalu Lintas Terhadap Dua Simpang Bersinyal Yang Berdekatan (Studi Kasus Simpang Empat Jalan KH.A Dahlan – Jalan Karimata – Jalan Johar dan Simpang Tiga Jalan KH.A Dahlan – Jalan Alianyang – Jalan KHW. Hasyim) Pontianak: Manajemen dan Rekayasa Lalu Lintas Terhadap Dua Simpang Bersinyal Yang Berdekatan (Studi Kasus Simpang Empat Jalan KH.A Dahlan – Jalan Karimata – Jalan Johar dan Simpang Tiga Jalan KH.A Dahlan – Jalan Alianyang – Jalan KHW. Hasyim) Pontianak - nernawani, nernwani; Rabihati, Etty; riyanti, rika (RETENSI, 2023)
The number of intersections with adjacent intersections in Pontianak City raises its own problems, one of which is the signalized intersection on Jalan KH. Ahmad Dahlan Pontianak. The short - term strategy to overcome these problems is traffic management and engineering to improve traffic flow based on field condition evaluation . Data collection was carried out by means of direct surveys at both intersections. The data obtained is used to obtain the existing conditions which will be a reference in planning a new cycle time by taking into account the coordination theory. Meanwhile, in calculating to get the best performance at each intersection, it is done using the MKJI approach. The best performance at each intersection is then coordinated using the green time between intersections. The results of the analysis of the performance of the existing conditions show that the degree of saturation is DS = 0.86 for signalized intersection 4 and DS = 0.68 for signalized intersection 3 which are not too different from what MKJI requires, DS = 0.75 , but it is not comfortable and safe to go through. From the queue length (QL) at the four intersection of 288 meters > the distance between the intersections which is 200 meters apart, and also from the delay time (DQ) of 66.03 seconds > from the green cycle time of 25 seconds, After knowing the performance of the existing intersection, then create a new cycle time planning for both intersections. The new cycle time with the best performance will be used to coordinate the two intersections. Selection of the best cycle time by comparing the values ​​of the degree of saturation (DS), the length of the queue (QL), and the delay (Delay) from several alternatives that were carried out. From the results of the study, a new cycle time of 95 seconds was obtained. The offset time used is 36 seconds, and the bandwidth from East to West and from West to East is 16 seconds. With the new cycle time the performance values ​​of the two intersections get better because the average delay and queue length decrease, for intersection 4 (DS = 0.76; QL = 136 m; DQ = 67 seconds) and intersection 3 (DS = 0, 67; QL = 94.5 m ; DQ = 65.37 seconds),